The Status of Digitisation in Europe - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The 2nd LIBER-EBLIDA Digitisation Workshop took place in The Hague between 19–21 October 2009 and was hosted by Bas Savenije as National Librarian of The Netherlands. In six sessions, the workshop considered a wide range of issues from business models to persistent identifiers. The papers were all of high quality, marking out the LIBER-EBLIDA Digitisation Workshop as the meeting to discuss pan-European digitisation issues. Four break-out groups helped to revise the LIBER Road Map for pan-European digitisation. Assessing the impact of the workshop, this paper identifies six top-level themes and questions to emerge from the three days of activity, which are summarised in the conclusions to this paper.